2018
DOI: 10.1159/000496374
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Menopause in Multiple Sclerosis Course: A Longitudinal Cohort Study

Abstract: Background: Hormonal variations are known to influence the course of multiple sclerosis (MS). Objectives: We aimed to evaluate the impact of menopause in MS course, including disease activity and disability progression. Methods: We conducted a retrospective longitudinal cohort study including all women, older than 44, post-menopausal, with a diagnosis of MS at least 1 year before menopause. We evaluated the impact of menopause in MS course comparing clinical and radiologic outcomes within 5 years before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…6 Ladeira et al and Baroncini et al also reported significant decrease in annual relapse rate after menopause. 6,256 On the other hand, Otero et al found that menopause did not influence the risk of disability accumulation when trajectories of EDSS over the complete disease course (from CIS through menopause) were accounted for, and once adjusting for age and disease duration. 72 Much of the ovarian aging biology accumulates years before the final menstrual cycle, highlighting a continuum of physiological changes, rather than any abrupt change arising at the final menstrual period that could influence MS course.…”
Section: Ovarian Aging and Disease Coursementioning
confidence: 85%
See 2 more Smart Citations
“…6 Ladeira et al and Baroncini et al also reported significant decrease in annual relapse rate after menopause. 6,256 On the other hand, Otero et al found that menopause did not influence the risk of disability accumulation when trajectories of EDSS over the complete disease course (from CIS through menopause) were accounted for, and once adjusting for age and disease duration. 72 Much of the ovarian aging biology accumulates years before the final menstrual cycle, highlighting a continuum of physiological changes, rather than any abrupt change arising at the final menstrual period that could influence MS course.…”
Section: Ovarian Aging and Disease Coursementioning
confidence: 85%
“…Ladeira et al detected stable EDSS variation across the menopausal transition 6. Ladeira et al and Baroncini et al also reported significant decrease in annual relapse rate after menopause 6,256.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This concept is further reinforced by the finding of a reduced risk of AD and improved cognitive function in post-menopausal women treated with 17β-estradiol (237,238). According to these observations, studies in MS showed that after menopause, the disease progresses more quickly (128,129,131), even though women have fewer relapses (129). As younger women with MS who underwent oophorectomy also found their disease getting worse after the procedure (128,131), this worsening of MS in natural or induced post-menopausal women is likely linked to the dropping of estrogen levels.…”
Section: Estrogens and Progesteronementioning
confidence: 96%
“…Additionally, in an online reproductive history survey of 513 patients with MS, women who underwent surgical menopause had greater patientreported disease severity as assessed by the MS Rating Scale (mean [SD] score: 13.1 [5.4]) compared with premenopausal women (mean [SD] score: 8.9 [5.5]; p < 0.0001 between groups); mean (SD) score for natural menopause was 9.6 (5.1) (18). A smaller retrospective study of 37 women with a diagnosis of MS prior to menopause supported declining relapse rate within 5 years after menopause (ARR: 0.08 vs. 0.37 before menopause; p < 0.001), but not increased disability, with no change reported after menopause for either EDSS progression rate (0.13-point increase per year both before and after menopause; p = 0.94) or frequency of EDSS progression events (37.8 vs. 48.6%; p = 0.42) (24). In a recent systematic review, when the data from the Baroncini et al (23) and Ladeira et al (24) studies were assessed in aggregate, no overall difference between relapse rates before and after menopause was found (risk ratio: 1.21; 95% CI, 0.91-1.61; p = 0.218) (25).…”
Section: Biology Of Menopause and Functioning In Msmentioning
confidence: 96%